Pengaruh Pemanfaatan Teknologi Informasi, Loyalitas, dan Work Life Balance Terhadap Kinerja Pegawai Aparatur Sipil Negara (ASN) Pada Masa Bekerja Dari Rumah Saat Pandemi Covid-19 Di Kementerian Pemberdayaan Perempuan dan Perlindungan Anak - Andhi Bharata (Jurnal Simki Economic, 2023)
The purpose of this study was to determine the effect of Utilization of Information Technology, Loyalty, and Work Life Balance on the performance of State Civil Apparatus (ASN) employees while working from home during the Covid-19 Pandemic at the Ministry of Women's Empowerment and Child Protection. This type of research is quantitative with data collection methods using survey techniques and distributing questionnaires. Questionnaires were distributed to 79 ASN employees at the Ministry of Women's Empowerment and Child Protection. The analysis of this study used IBM SPSS Statistics 25. The results showed that there was a simultaneous positive and significant effect of Information Technology Utilization, Loyalty, and Work Life Balance on the Performance of ASN employees at the Ministry of Women's Empowerment and Child Protection.